Wireless local area network (WLAN) / Raja Fazrin Raja Muhamad - Raja Muhamad, Raja Fazrin (1999)
This paper describes the networking requirements in typical applications for wireless network. In particular the wireless medium access control (MAC) protocol is investigated. Beside distributed-queueing request update multiple access (DQRUMA) protocol other wireless MAC protocol are also considered. The main feature of MAC protocol is to support multiple users in wireless environment The first chapter provides an introduction to the wireless network, followed by chapter two, we more focus about wireless medium access control (MAC) protocol and in chapter three is more to DQRUMA protocol simulation model. However, in this paper the main objective of the study is to evaluate the performance of DQRUMA protocol. The protocol is simulated using the commercial communication software design tool.